2010
DOI: 10.3109/01421590903514614
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of behavior change counseling education for medical students

Abstract: Background: Educating medical students about how to effectively counsel patients with negative health behaviors (i.e., lack of exercise, smoking) is vitally important. Behavior change counseling is a promising method that can be used by physicians to encourage positive changes in health behaviors. Purpose: To examine the effectiveness of a 2 h workshop in behavior change counseling for medical students. Methods: This study used a pre-post control group design with 35 second-year medical students who were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…5,22,23 Each of these tools is described in detail herein, and copies may be requested from the corresponding author. Raters were paid pharmacists recruited from a pool of evaluators who had previously facilitated or participated in the practice laboratories and practica for the course.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…5,22,23 Each of these tools is described in detail herein, and copies may be requested from the corresponding author. Raters were paid pharmacists recruited from a pool of evaluators who had previously facilitated or participated in the practice laboratories and practica for the course.…”
Section: Designmentioning
confidence: 99%
“…Student ability was measured using a validated instrument, student knowledge through pretests and posttests, and confidence through survey tools. 5,22,23 This quasi-experimental study used a double-blinded controlled design including both qualitative and quantitative methods. The university's Institutional Review Board approved the research as exempt from full board review, as the risk to participants was none or minimal.…”
Section: Designmentioning
confidence: 99%
“…Ryu et al 4) reported that Korean dental hygiene students have a strong Moreover, given similar levels of effects, it was reported that it would be clinically more efficient to employ role-play, given its potential for reducing costs and easy applications. Therefore, role-play practice is often employed in clinical studies as it is easy to apply 8,18) .Given that there have been spotlights on the communication competency training, it is necessary to provide such training at the college level. As such, this study aimed to apply the principle of MI training on dental hygiene, without its application to any other models.…”
mentioning
confidence: 99%
“…Ryu et al 4) reported that Korean dental hygiene students have a strong Moreover, given similar levels of effects, it was reported that it would be clinically more efficient to employ role-play, given its potential for reducing costs and easy applications. Therefore, role-play practice is often employed in clinical studies as it is easy to apply 8,18) .…”
mentioning
confidence: 99%
See 1 more Smart Citation